Magnetic resonance imaging of the upper airway structure of children with obstructive sleep apnea syndrome. - Arens, R; McDonough, J M; Costarino, A T; Mahboubi, S; Tayag-Kier, C E; Maislin, G; Schwab, R J; Pack, A I (American Journal of Respiratory & Critical Care Medicine)
The anatomical relationships between lymphoid, bony, and other tissues affecting the shape of the upper airway in children with obstructive sleep apnea syndrome (OSAS) have not been established. We therefore compared the upper airway structure in 18 young children with OSAS (age 4.8 +/- 2.1 yr; 12 males and 6 females) and an apnea index of 4.3 +/- 3.9, with 18 matched control subjects (age, 4.9 +/- 2.0 yr; 12 males and 6 females). All subjects underwent magnetic resonance imaging under sedation. Axial and sagittal T1- and T2-weighted sequences were obtained. Images were analyzed with image-processing software to obtain linear, area, and volumetric measurements of the upper airway and the tissues comprising the airway. The volume of the upper airway was smaller in subjects with OSAS in comparison with control subjects (1.5 +/- 0.8 versus 2.5 +/- 1.2 cm(3); p < 0.005) and the adenoid and tonsils were larger (9.9 +/- 3.9 and 9.1 +/- 2.9 cm(3) versus 6.4 +/- 2.3 and 5.8 +/- 2.2 cm(3); p < 0.005 and p < 0.0005, respectively). Volumes of the mandible and tongue were similar in both groups; however, the soft palate was larger in subjects with OSAS (3.5 +/- 1.1 versus 2.7 +/- 1.2 cm(3); p < 0.05). We conclude that in children with moderate OSAS, the upper airway is restricted both by the adenoid and tonsils; however, the soft palate is also larger in this group, adding further restriction.